Preliminary Investigations on the Reduction of Foot Pressure Measurement and Muscle Activity with Different Insole Materials - Isa, Halim (Trans Tech Publications, 2012)
Standing for long periods of time has been recognized as a potential contributor to muscle fatigue. When a person is performing activities in prolonged standing and wearing ineffective material of shoe insole, not only lead to muscle fatigue but can even cause injuries in the long term. The objective of this study is to determine the effects of two types of shoe insole materials; Ethylene Vinyl Acetate (EVA) and a combination of polyurethane (PU) and poron on muscle activity and foot pressure. The analysis of muscle fatigue was performed using surface electromyography (sEMG) while pressure under the foot was measured using FScan device. Results of comparison found that the two types of shoe insole materials showed significant difference (pvalue < 0.05) in electromyography signals (μV) in the left and right gastrocnemius muscle while there are significant reductions on the peak pressure measured from the foot pressure measurement. It can be concluded that the combination of PU and poron is an effective material to be used a shoe insole for a person who is exposed to prolonged periods of standing.